Peningkatan Keterampilan Menulis Karangan dengan Menggunakan Media Gambar Seri pada Siswa Kelas IV SD Negeri Perumnas Kota Makassar - Herlina Herlina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: Improving Writing Skills by Using Image Media Series pthere are Students of Class IV SD Negeri Perumnas Kota Makassar. This study aims to determine the improvement of essay writing skills using series image media in grade IV students of SD Negeri Kota Makassar. The type of researchused is class action research (PTK) according to Arikunto (2008: 16) which consists of four activities, namely including the planning stage, implementation stage, observation, and reflection. Suby ekin this study are class IV teachers and all grade IV students of SD Negeri Perumnas Kota Makassar. Data collection techniques are carried out through observation sheets, namely direct observation of activities carried out by teachers in the learning process and student activities during learning activities, tests to measure student abilities and documentation in this study consisting of syllabus, rpp, daily scores and photos. Based on the results of the final test of the first action cycle, students' classical mastery of the essay writing material is not complete and has not been successful because it is still below the KKM standard score, this is because students have not been able to write essays based on series drawings and only some students determine the theme of the essay that has been made. Phase II cycle II use of series image media can be carried out properly, this can be seen in the final test results of cycle II. Thus, there was an increase in essay writing skills using series image media in grade IV students of SD Negeri Perumnas Kota Makassar to achieve a minima l completion score.